O herói Sepé em duas versões : O Uraguai e Sepé - o morubixaba rebelde - Oliveira, Ellen dos Santos (2016)
This paper presents Sepé. Also famous hero, from the perspective of literary heritage left by Basilio da Gama, in the Uraguai (1769), but as points Bakhtin (1981), an emblematic figure of a historical universe, mythical and cultural beyond the scope of this heritage gaining independence such that allows you to cycle through historical events, artistic and diverse literary. One of these manifestations is Sepe, the rebel morubixaba (1964), Fernandes Barbosa, part of a group of literary productions whose base (re) of the Indian story-telling Sepé Tiaraju, since for 144 years the only literary version known was the range. These works are The lunar Sepe (1913), poem Simoes Lopes Neto, Tiaraju (1945), historical novel Manoellito of Ornella, the mainland (1949), a novel by Erico Verissimo, Sepe - the rebel morubixaba (1964), poem epic Fernandes Barbosa, and Sepé Tiaraju - Romance of the Seven Peoples Mission (1975), novel Alcy Cheuiche, whose version is adapted to comics. Note, with such productions, a landmark move that paves the way for a vast cultural artistic production recognition and reaffirmation of the Indian heroism. Conceiving Sepe, the rebel morubixaba as a hypertext The Uraguai, believing that the story of Sepé Tiaraju out distorted by Basilio da Gama, Fernandes Barbosa rewrites the history of the Indian hero, giving it a new meaning and new life. In his rewriting, it uses several tricks to give the work a garment and a feature that the poet believes, are worthy of the indigenous hero Sepé Tiaraju, the warrior Lunar. Therefore, this work is intended to make a comparative reading between two literary works, one of the eighteenth century, the Uraguai, and one twentieth, Sepe - the rebel morubixaba, and from that read, analyze and explore the profile of hero these two epic poems, watching as the modern epic dialogues with the neoclassical epic, is to rewrite it, is to overcome it. This highlights the mimetic character, in the sense of emulation, the literary text. This is when a writer is motivated to imitate another, either to match up or overcome it. In the case studied, Fernandes mimics Gama, when writing his epic poem based on the story of Sepé Tiaraju in order to overcome it. With his attempt he just entering his poem in the national epic tradition. This work addressed the contemporary theory of the epic developed by Anazildo Silva (1984), and treated by Ramalho and Silva (2007); Ramalho (2013); Silva (2012); and Neiva (2009; 2012). Were also worked the concepts of dialogism Bakhtin (1981; 1997; 2006), intertextuality Kristeva (1974), hypertextuality of Genette (2010), among others. On the historical, social and cultural context were useful studies developed by Candido (1984; 1999; 2006a; 2006b), Teixeira (1999), Verney (1952), Oliveira (2010), Nunes (2013), Rue (2009) Carvalho (1987), among others.